Bullying and Cyberbullying Are Associated with Low Levels of Motivational Beliefs Toward Learning in Youth - Jose Luis Solas-Martínez; Rubén Roldán-Roldán; María de las Nieves Moyano-Muñoz; Emilio J. Martínez-López (European Journal of Investigation in Health, Psychology and Education, 2025)
This study explored the association between bullying and cyberbullying, both in victims and bullies, and motivational beliefs toward learning in students aged 10 to 16. A cross-sectional study was conducted with 1690 Spanish students, assessing motivational beliefs through the Motivated Strategies for Learning Questionnaire (MSLQ) and involvement in bullying using the European Bullying Intervention Project Questionnaire (EBIP-Q) and the European Cyberbullying Intervention Project Questionnaire (ECIP-Q). The results showed that both victims and bullies had lower task value, self-efficacy, and control beliefs, along with higher test anxiety, with cyberbullying having a stronger impact. Victims of cyberbullying exhibited significantly lower task value (up to 9.2% in girls and 5.6% in boys) and had a 4.5- and 2.2-times higher risk of scoring low in this dimension. Among bullies, only girls involved in traditional bullying showed motivational deficits, whereas both male and female cyberbullies had task value scores up to 9.5% lower and were 1.5 to 1.6 times more likely to experience test anxiety. These findings emphasize the need for targeted interventions to reinforce motivational beliefs in victims and bullies, recommending collaborative programs between students, teachers, and families to enhance task value, control beliefs, and self-efficacy while addressing test anxiety.